2016
DOI: 10.1111/bjh.14295
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of acute graft‐versus‐host disease: from intestinal microbiota alterations to donor T cell activation

Abstract: Acute graft-versus-host disease (aGVHD) is a major life-threatening complication of allogeneic haematopoietic cell transplantation (allo-HCT). Here we discuss the aGVHD pathophysiology initiated by multiple signals that cause alloreactive T-cell activation. The outcome of such donor T-cell activation is influenced by T-cell receptor-signal strength, anatomical location, co-stimulatory/co-inhibitory signals and differentiation stage (naive, effector/memory) of T-cells. Additionally, cross-priming of T cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 174 publications
(204 reference statements)
0
93
0
2
Order By: Relevance
“…The immune-mediated destruction of the intestinal mucosa leads to a failure of fluid resorption, particularly in the ileum, and is largely responsible for voluminous diarrhoea in patients with acute GVHD 22,23 . In addition, the destruction of mucosal cells at the brush border and consequent reduction in luminal levels of disaccharidase enzymes creates an osmotic effect due to the passage of unabsorbed carbohydrates 22,23 . Dysbiosis depletes the gut of bacterial populations, which might otherwise mitigate this effect via metabolism of these luminal polysaccharides 23 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The immune-mediated destruction of the intestinal mucosa leads to a failure of fluid resorption, particularly in the ileum, and is largely responsible for voluminous diarrhoea in patients with acute GVHD 22,23 . In addition, the destruction of mucosal cells at the brush border and consequent reduction in luminal levels of disaccharidase enzymes creates an osmotic effect due to the passage of unabsorbed carbohydrates 22,23 . Dysbiosis depletes the gut of bacterial populations, which might otherwise mitigate this effect via metabolism of these luminal polysaccharides 23 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…In addition, the destruction of mucosal cells at the brush border and consequent reduction in luminal levels of disaccharidase enzymes creates an osmotic effect due to the passage of unabsorbed carbohydrates 22,23 . Dysbiosis depletes the gut of bacterial populations, which might otherwise mitigate this effect via metabolism of these luminal polysaccharides 23 . Furthermore, compromise of brush border tight junctions (also known as zonulae occludentes) in the setting of a vigorous inflammatory response can lead to substantial mucosal protein loss, therefore drawing fluid into the intestinal lumen via oncotic pressure 24 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…8, [17][18][19][20] In HLA-matched sibling HCT, T-cell alloreactivity is directed against mHAgs, that is, polymorphic non-self-peptides encoded anywhere in the human genome. 9,[11][12][13] Allorecognition of mHAgs is mediated by conventional self-HLA-restricted, foreign peptide-specific T cells whose repertoire is shaped by positive and negative selection in the thymus.…”
Section: Introductionmentioning
confidence: 99%
“…Graft-versus-host disease is a complex biological process, which includes severe immune dysregulation with sustained inflammation (4). Several studies have identified interleukin-6 (IL-6) and as an important factor in the pathophysiology of GVHD (5, 6).…”
Section: Introductionmentioning
confidence: 99%